The Teleoperation of Robot Arms by Interacting with an Object’s Digital Twin in a Mixed Reality Environment - Yan Wu; Bin Zhao; Qi Li (Applied Sciences)
The teleoperation of robot arms can prevent users from working in hazardous environments, but current teleoperation uses a 2D display and controls the end effector of robot arms, which introduces the problem of a limited view and complex operations. In this study, a teleoperation method for robot arms is proposed, which can control the robot arm by interacting with the digital twins of objects. Based on the objects in the workspace, this method generates a virtual scene containing digital twins. Users can observe the virtual scene from any direction and move the digital twins of the objects at will to control the robot arm. This study compared the proposed method and the traditional method, which uses a 2D display and a game controller, through a pick-and-place task. The proposed method achieved 45% lower scores in NASA-TLX and 31% higher scores in SUS than traditional teleoperation methods. The results indicate that the proposed method can reduce the workload and improve the usability of teleoperation.